2018
DOI: 10.3906/sag-1712-188
|View full text |Cite
|
Sign up to set email alerts
|

What has changed in the utility of pediatric EEG over the last decade?

Abstract: Background/aim: We evaluated the utility of electroencephalography (EEG) in children with neurological conditions and compared the results with those of our previous study on excessive uses of pediatric EEG, which was published in 2003. We also evaluated the possibility of subsequent EEGs and satisfactory duration of EEG recordings according to EEG type and admission status. We also evaluated the yield of varying durations of EEG recordings.Materials and methods: All consecutive pediatric EEG records performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…We think that only EEG is requested by a pediatric neurologist in our clinic increases this rate. In the other two studies conducted in Turkey, the rate of finding epileptic in headache is very different from each other, such as 11.6% and 4% (4,5). In our study, a higher result of 19% was found.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…We think that only EEG is requested by a pediatric neurologist in our clinic increases this rate. In the other two studies conducted in Turkey, the rate of finding epileptic in headache is very different from each other, such as 11.6% and 4% (4,5). In our study, a higher result of 19% was found.…”
Section: Discussioncontrasting
confidence: 82%
“…In the study of Orgun et al (4), when the EEG was evaluated according to the reasons for the request, it was found to be epileptic at a rate of 8.5% in FS, 16% in tic, 15.7% in speech disorder, 44% in learning disability, 20% in sleep disorder, 11% in night terror, 10% in breath holding spells, 8.4% in syncope, and 11.6% in headache.…”
Section: Discussionmentioning
confidence: 99%